Features of mechanical jaundice course caused by complications of bile disease - V. E. Fedorov; B. S. Haritonov; V. V. Masljakov; O. E. Logvina; M. A. Naryzhnaja (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was improving the results of diagnostics and assessment of the severity of patients with mechanical jaundice (MJ) at various stages of its development.METHODS AND MATERIALS. The basis of clinical and laboratory research was the data of 537 patients who were admitted during the period from 2010 to 2019. Principles of separation at the stage of the course of mechanical jaundice of non-tumor Genesis.RESULTS. Analysis of clinical and laboratory studies showed characteristic signs of various complications of cholelithiasis, accompanied by mechanical jaundice. Then, on this basis, specific symptoms characteristic of each stage of mechanical jaundice of non-tumor Genesis were determined.CONCLUSION. The course of mechanical jaundice, which develops with complications of cholelithiasis, has a phase-stage character, beginning with extrahepatic cholestasis, then-joining hepatocytolysis and ending with cholangitis. Initially, cholestasis and cytolysis are functional, which is confirmed by biochemical tests, so these processes are labile and reversible. This makes it possible to effectively use biliary decompression methods and infusion therapy with detoxification during treatment. Cholangitis is characterized by destructive morphological manifestations, so it is verified by specific clinical symptoms and laboratory tests characteristic of inflammatory-septic reactions and progresses to sepsis. Differentiation of stages of mechanical jaundice allows to personify surgical and conservative treatment of such patients.